Optimization of microstructured hollow ﬁber design for membrane distillation applications using CFD modeling - Yang, Xing (2013)
This study explores the potential of microstructured hollow ﬁber designs to enhance process performance in a direct contact membrane distillation (DCMD) system. Hollow ﬁbers with 10 different geometries (wavy- and gear-shaped cross sections) were evaluated. A series of three-dimensional computational ﬂuid dynamic (CFD) simulations were carried out to investigate their capability in terms of depolarizing the buildup of liquid boundary layers, thus improving water productivity. Analyses of heat and mass transfer as well as the ﬂow-ﬁeld distribution in respective MD modules were obtained. It was found that the enhancement of the heat-transfer coefﬁcients, hf, was up to 4.5-fold for a module with a wavy ﬁber design 07 and an approximate 5.5-fold hp increase for a gear-shaped ﬁber design. The average temperature polarization coefﬁcient and mass ﬂux Nm of the gear-shaped ﬁber module showed an improvement of 57% and 66%, respectively, over the original straight ﬁber design, followed by the wavy designs 07 and 08. The enhanced module performance was attributed to the improved hydrodynamics through the ﬂow channels of various ﬁber geometries, which was conﬁrmed by the visualization of ﬂow-ﬁeld and temperature proﬁles in CFD. Investigations of the ﬁber-length effect showed that the gear-shaped ﬁber modules exhibited the highest ﬂux enhancement of 57–65% with the same length, compared to the modules with original straight and wavy ﬁbers. In addition, the gear-shaped ﬁber module is very sensitive to feed velocity changes. Therefore, employing a smart microstructured design on the membrane surface would bring in a signiﬁcant improvement under adverse ﬂow conditions. Moreover, the computed water production and hydraulic energy consumption (HEC) among the modules with various ﬁber geometries were compared. With 1.9-fold surface area increase per unit volume, the gear-shaped ﬁber conﬁguration had the highest water production but the lowest HEC, followed by wavy designs 07 and 08.